Helena the horse-riding fairy - Meadows, Daisy (New York : Scholastic Inc., 2010)
While everyone in Fairyland is getting ready for the Fairy Olympics, Jack Frost's goblins steal the Sports Fairies' magic objects and mix the stables all up. Can Rachel and Kirsty help Helena the Horseriding Fairy rein things in?
Originally published with series title The sports fairies : London : Orchard Books, 2008.
RL: 2.
Ages 6-9.
Accelerated Reader
Keywords: Walker, Rachel (Fictitious character) -- Juvenile fiction; Tate, Kirsty (Fictitious character) -- Juvenile fiction; Fairies -- Juvenile fiction; Horses -- Juvenile fiction; Olympics -- Juvenile fiction; Magic -- Juvenile fiction; Jack Frost (Legendary character) -- Juvenile fiction; Goblins -- Juvenile fiction; Fairies; Goblins; Horses; Jack Frost (Legendary character); Magic; Olympics; Sports stories; Tate, Kirsty (Fictitious character); Walker, Rachel (Fictitious character); JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Social Themes / Friendship; Sports fiction; Fiction; Juvenile works; Fantasy fiction